Microstructure manipulation by laser-surface remelting of a full-Heusler compound to enhance thermoelectric properties. (15th January 2022) - Gomell, Leonie; Haeger, Tobias; Roscher, Moritz; Bishara, Hanna; Heiderhoff, Ralf; Riedl, Thomas; Scheu, Christina; Gault, Baptiste
Abstract: There is an increasing reckoning that the thermoelectric performance of a material is dependent on its microstructure. However, the microstructure-properties relationship often remains elusive, in part due to the complexity of the hierarchy and scales of features that influence transport properties. Here, we focus on the Heusler-Fe2 VAl compound, which shows promising thermoelectric properties, is non-toxic, cheap, and consist of earth-abundant elements. We directly correlate microstructure and local properties, using advanced scanning electron microscopy methods including in-situ four-point-probe technique for electron transport measurements. The local thermal conductivity is investigated by scanning thermal microscopy. Finally, atom probe tomography provides near-atomic scale compositional analysis. To locally manipulate the microstructure, we use laser surface remelting. The rapid quenching creates a complex microstructure with a high density of dislocations and small, elongated grains. We hence showcase that laser surface remelting can be employed to manipulate the microstructure to reduce the thermal conductivity and electrical resistivity, leading to a demonstrated enhancement of the thermoelectric performance at room temperature. Graphical abstarct: Image, graphical abstract